Increased hepatic stiffness as consequence of high hepatic afterload in the fontan circulation: A vascular doppler and elastography study. Issue 1 (19th November 2013) - Kutty, Shaija S.; Peng, Qinghai; Danford, David A.; Fletcher, Scott E.; Perry, Deborah; Talmon, Geoffrey A.; Scott, Cynthia; Kugler, John D.; Duncan, Kim F.; Quiros‐Tejeira, Ruben E.; Kutty, Shelby; ,
<x xml:space="preserve">Abstract</x> Hepatic dysfunction is a recognized complication after Fontan palliation of congenital heart disease. We sought to quantitatively measure hepatic stiffness and vascular Doppler indices using ultrasound (US) and shear wave elastography (SWE) in a Fontan cohort. Subjects were prospectively recruited for echocardiography and real‐time hepatic duplex US with SWE for hepatic stiffness (kPa). Doppler peak velocities, velocity time integral, resistive, pulsatility, acceleration indices (RI, PI, AI), and flow volume were measured in celiac artery, superior mesenteric artery, and main portal vein (MPV). A subset underwent cardiac catheterizations with liver biopsy. Correlations were explored between SWE, duplex, hemodynamic, and histopathologic data. In all, 106 subjects were studied including 41 patients with Fontan physiology (age 13.8 ± 6 years, weight 45.4 ± 23 kg) and 65 controls (age 15.0 ± 8.4 years, weight 47.9 ± 22 kg). Patients with Fontan physiology had significantly higher hepatic stiffness (15.6 versus 5.5 kPa, P < 0.0001), higher celiac RI (0.78 versus 0.73, P = 0.04) superior mesenteric artery RI (0.89 versus 0.84, P = 0.005), and celiac PI (1.87 versus 1.6, P = 0.034); while MPV flow volume (287 versus 420 mL/min in controls, P = 0.007) and SMA AI (829 versus 1100, P = 0.002) were lower. Significant correlation was seen for stiffness with ventricular end‐diastolic pressure (P = 0.001) and pulmonary artery wedge pressure (P = 0.009). Greater stiffness correlated with greater degrees of histopathologic fibrosis. No significant change was seen in stiffness or other duplex indices with age, gender, time since Fontan, or ventricular morphology. Conclusion: Elevated hepatic afterload in Fontan, manifested by high ventricular end‐diastolic pressures and pulmonary arterial wedge pressures, is associated with remarkably increased hepatic stiffness, abnormal vascular flow patterns, and fibrotic histologic changes. The MPV is dilated and carries decreased flow volume, while the celiac and superior mesenteric arterial RI is increased. SWE is feasible in this population and shows promise as a means for predicting disease severity on liver biopsy. (Hepatology 2014;58:251–260)